Child health promotion during the COVID-19 pandemic: A health and welfare sector collaboration - Nompumelelo Ntshingila; Alida S. du Plessis-Faurie (AOSIS, 2023)
Background: Fragmented service provision and a lack of efficient cooperation between health and welfare sectors serving children and families remain ongoing challenges in South Africa. The coronavirus disease 2019 (COVID-19) pandemic escalated this fragmentation. A community of practice (CoP) was established by the Centre for Social Development in Africa to promote collaboration between the sectors and to assist communities in their environments. Aim: To explore and describe collaboration on child health promotion between professional nurses and social workers, who formed part of the CoP during the COVID-19 pandemic. Setting: The study was conducted in five public schools from four of the seven district regions of the City of Johannesburg, Gauteng province. Methods: A qualitative, exploratory, descriptive research design was employed to conduct psychosocial and health screenings of children and their families. Focus group interviews were conducted, and field notes were used to collect and confirm data from the team. Results: Four themes emerged. Participants shared their positive and negative experiences faced during the fieldwork, their realisation of the value of collaboration between various sectors and their desire and capacity to do more. Conclusion: Participants indicated that collaboration between the health and welfare sectors is vital to support and promote the health of children and their families. The COVID-19 pandemic highlighted the need for collaboration between these sectors in the children and their families' ongoing struggles. Contribution: The importance of these sectors being engaged as a team highlighted the multisectoral influence shaping child development outcomes, supporting children's human rights and advancing social and economic justice.